Ramadhani, Subhi KONSEP TAZKIYATUN NAFS DALAM KIDUNG WAHYU KOLOSEBO KARYA SRI NARENDRA KALASEBA - Wisnu Mahendra Ramadhani; Muhammad Rifa'i Subhi (Yayasan Haiah Nusratul Islam, Indonesia, 2025)
This study explores the concept of Tazkiyatun Nafs (spiritual purification) in Kidung Wahyu Kolosebo by Sri Narendra Kalaseba as a form of integration between Islamic spirituality and Javanese culture. Using a qualitative approach with hermeneutic and Sufistic methods, the research interprets the symbolism and spiritual meaning contained in the song’s lyrics in relation to Imam al-Ghazali’s Sufi teachings, particularly the three stages of soul purification: Takhalli (emptying oneself of negative traits), Tahalli (adorning oneself with virtuous qualities), and Tajalli (divine illumination). The findings reveal that Kidung Wahyu Kolosebo serves not merely as a cultural artifact of aesthetic value but also as a medium of da’wah and spiritual education, guiding individuals to control their desires, cultivate noble character, and attain closeness to Allah SWT. Its lyrics portray the inner journey from self-restraint to spiritual enlightenment, symbolized by the phrase “wahyu kolosebo,” representing the unification of the servant’s will with the Divine will. This study concludes that Javanese traditional literature can function as an effective medium for moral and spiritual development in contemporary society, demonstrating harmony between Sufi values and the local wisdom of the Nusantara.